Thyroid function is associated with non-alcoholic fatty liver disease in euthyroid subjects. (May 2015) - Tao, Yang; Gu, Hongbing; Wu, Jingcheng; Sui, Jian
Abstract Objectives: This study was designed to test the hypothesis that normal thyroid function is associated with non-alcoholic fatty liver disease (NAFLD) in euthyroid general subjects. Methods: A total of 739 euthyroid subjects were enrolled in this cross-sectional study. Using ultrasound, a diagnosis of NAFLD was made in subjects without a history of excessive alcohol consumption or liver diseases. Fasting serum samples were collected for determining thyroid function [thyroid-stimulating hormone (TSH), free thyroxine (FT4), and free triiodothyronine (FT3) levels] and other biochemical parameters. Results: Among the enrolled subjects, 196 (26.5%) satisfied the diagnostic criteria for NAFLD. Subjects with NAFLD had significantly higher TSH levels and lower FT4 levels than those without NAFLD (p < 0.01 for both). NAFLD prevalence increased gradually with increasing quartiles of TSH levels and decreasing quartiles of FT4 levels. After adjustment for gender and age, TSH levels were found to correlate positively with body mass index (BMI), waist circumference (WC), and LDL-cholesterol levels (p < 0.05 for all) and negatively with HDL-cholesterol levels (p < 0.01). FT4 levels correlated negatively with both BMI and WC (p < 0.05 for both). Multiple logistic regression analysis showed that TSH and FT4 levels were independent risk factors for NAFLD [odds ratio (OR): 2.21, 95% confidence interval (CI): 1.21–4.02, p = 0.01, for TSH levels; OR: 0.39, 95% CI: 0.17–0.87, p = 0.02, for FT4 levels]. Conclusion: Our findings suggest that serum FT4 and TSH levels, even those within the reference range, are associated with NAFLD in the general population, independent of known metabolic risk factors.